Navigating the Non-Native Planting Rule: Permit Requirements for Large-Scale Plantings of Non-Native Species in Florida - Deah Lieurance; Eric Rohrig; Stephen Enloe (EDIS, 2021)
This fact sheet discusses why plantings of non-native plants are regulated, describes how plantings are regulated in Florida, and shows how the UF/IFAS Assessment of Non-Native Plants in Florida’s Natural Areas is critical to this process. Written by Deah Lieurance, Eric Rohrig, and Stephen Enloe, and published by the UF/IFAS Agronomy Department, June 2021.